Herpes simplex ICP27 mutant viruses exhibit reduced expression of specific DNA replication genes. - Uprichard, S L (1996)
Herpes simplex virus type 1 mutants with certain lesions in the ICP27 gene show a 5- to 10-fold reduction in viral DNA synthesis. To determine how ICP27 promotes amplification of viral DNA, we examined the synthesis, accumulation, and stability of the essential viral replication proteins and steady-state levels of the replication gene transcripts throughout the course of ICP27 mutant virus infections. These studies reveal that in the absence of ICP27, expression of the UL5, UL8, UL52, UL9, UL42, and UL30 genes is significantly reduced at the level of mRNA accumulation. In contrast to that of these beta genes, ICP8 expression is unaltered in mutant virus-infected cells, indicating that ICP27 selectively stimulates only a subset of herpes simplex virus beta genes. Analysis of multiple ICP27 mutant viruses indicates a quantitative correlation between the ability of these mutants to replicate viral DNA and the level of replication proteins produced by each mutant. Therefore, we conclude that the primary defect responsible for restricted viral DNA synthesis in cells infected with ICP27 mutants is insufficient expression of most of the essential replication genes. Of further interest, this analysis also provides new information about the structure of the UL52 gene transcripts.